The Dynamics of Pesantren Curriculum Reform in Integrating General and Religious Knowledge Towards a Balanced Curriculum Design - Mubarok, Ikhsan; Nadhir, Mirbahun (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Rapid social and technological developments have driven transformations in Islamic education systems, particularly within pesantren institutions. Specific Background: Traditionally characterized by a textual-conservative orientation, pesantren curricula are increasingly adapting to integrate general knowledge, religious studies, and digital literacy. Knowledge Gap: However, empirical evidence on how this integration produces a balanced and adaptive curriculum design remains limited. Aims: This study aims to analyze the dynamics of pesantren curriculum reform in integrating general and religious knowledge toward a balanced curriculum design responsive to global changes. Results: Using a qualitative case study approach with data collected through in-depth interviews, participatory observation, and documentation, and analyzed via the Miles and Huberman interactive model, the findings reveal a paradigm shift toward an integrative and contextual learning model. This shift has produced a hybrid curriculum combining religious scholarship, general education, and digital competencies, ensuring both relevance to 21st-century skill demands and continuity of Islamic intellectual traditions. Novelty: The study offers an empirical model of hybrid curriculum reform within pesantren, demonstrating a structured integration of diverse knowledge domains. Implications: These findings provide a reference framework for policymakers and practitioners in developing adaptive and balanced Islamic education systems aligned with contemporary global challenges. Highlights: Paradigm transition from conservative textual learning to contextual integrative models. Hybrid structure combining religious scholarship, general studies, and digital competencies. Empirical framework proposed for adaptive Islamic education development. Keywords: Pesantren Curriculum, Knowledge Integration, Islamic Education, Hybrid Curriculum, Global Disruption.